Auditory and otologic profile of Alström syndrome: Comprehensive single center data on 38 patients. Issue 8 (1st June 2017) - Lindsey, Spencer; Brewer, Carmen; Stakhovskaya, Olga; Kim, Hung Jeffrey; Zalewski, Chris; Bryant, Joy; King, Kelly A.; Naggert, Jürgen K.; Gahl, William A.; Marshall, Jan D.; Gunay‐Aygun, Meral
Abstract : Alström syndrome (AS) is a rare autosomal recessive ciliopathy caused by mutations in the ALMS1 gene. Hallmark characteristics include childhood onset of severe retinal degeneration, sensorineural hearing loss, obesity, insulin‐resistant diabetes, and cardiomyopathy. Here we comprehensively characterize the auditory and otologic manifestations in a prospective case series of 38 individuals, aged 1.7–37.9 years, with genetically confirmed AS. Hearing loss was preceded by retinal dystrophy in all cases, and had an average age of detection of 7.45 years (range 1.5–15). Audiometric assessments showed mean pure tone averages (0.5, 1, 2, 4 kHz) of 48.6 and 47.5 dB HL in the right and left ears, respectively. Hearing was within normal limits for only 8/74 ears (11%). For the 66 ears with hearing loss, the degree was mild (12%), moderate (54%), or severe (8%). Type of hearing loss was predominantly sensorineural (77%), while three ears had mixed loss, no ears had conductive loss, and type of hearing loss was indeterminate for the remaining 12 ears. Serial audiograms available for 33 patients showed hearing loss progression of approximately 10–15 dB/decade. Our data show that hearing loss associated with AS begins in childhood and is a predominantly symmetric, sensory hearing loss that may progress to a severe degree. Absent otoacoustic emissions, intact speech discrimination, and disproportionately normal auditory brainstem responses suggest an outer hair cell site of lesion. These findings indicate that individuals with AS would benefit from sound amplification and if necessary, cochlear implantation.